1996
DOI: 10.1136/fn.75.1.f42
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal hypothermia and cold stress among newborn infants in Nepal monitored by continuous ambulatory recording.

Abstract: Aims-To describe the pattern of hypothermia and cold stress after delivery among a normal neonatal population in Nepal; to provide practical advice for improving thermal care in a resource limited maternity hospital. Methods-The principal government funded maternity hospital in Kathmandu, Nepal, with an annual delivery rate of 15 000 (constituting 400/o of all Kathmandu Valley deliveries), severe resource limitations (annual budget £250 000), and a cold winter climate provided the setting. Thirty five healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 6 publications
0
33
0
1
Order By: Relevance
“…Studies in Nepal using continuous temperature monitoring have indicated that thermal stress may be extremely common among newborn infants; 80% of hospital-born infants became hypothermic soon after birth. 472 In another maternity hospital study in Nepal, 85% of newborns had a temperature Ͻ36°C within 2 hours of birth. 473 Similarly, in facility-based studies in Ethiopia, 474 Zambia, 475 and Zimbabwe, 476 one half to two thirds of newborns had hypothermia.…”
Section: Hypothermia Prevention and Managementmentioning
confidence: 99%
“…Studies in Nepal using continuous temperature monitoring have indicated that thermal stress may be extremely common among newborn infants; 80% of hospital-born infants became hypothermic soon after birth. 472 In another maternity hospital study in Nepal, 85% of newborns had a temperature Ͻ36°C within 2 hours of birth. 473 Similarly, in facility-based studies in Ethiopia, 474 Zambia, 475 and Zimbabwe, 476 one half to two thirds of newborns had hypothermia.…”
Section: Hypothermia Prevention and Managementmentioning
confidence: 99%
“…Perinatal mortality rates are considerably higher in low-income regions (57 per 1000 total births) than in highincome regions (11 per 1000) (WHO 1996b). We predicted that the prevalence of encephalopathy would likewise be higher and that concurrent adverse perinatal factors common in low-income countries such as neonatal hypothermia (Ellis et al 1996), hypoglycaemia (Anderson et al 1993), and late neonatal infection (Jalil et al 1993) might affect outcome. This study reports on the 1-year outcome of a cohort of term infants with NE who were recruited during an 18-month study.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] These studies were mainly carried out in a controlled optimal environment. 6,7 In contrast, in developing countries the environment in the delivery rooms (DRs) is uncontrolled. 8,9 Studies in developing countries, including India, have demonstrated high incidence of hypothermia in neonatal period.…”
Section: Introductionmentioning
confidence: 99%